Natural Products as Sources of Antimalarial Drugs: Ethnobotanical and Ethnopharmacological Studies - Oluwole Solomon Oladeji; Abimbola Peter Oluyori; Deborah Temitope Bankole; Tokunbo Yemisi Afolabi (Scientifica)
Ethnopharmacological Relevance. Malaria is one of the lethal diseases of man, contributing to about 17 million deaths annually, leading to sociocultural, economic, and health influences. Aim of the Study. The study explores the ethnobotanical and ethnopharmacological appraisal of antimalarial plants used by people of Omu Aran, Ogbomoso, Ado Ekiti, and Sagamu communities in Nigeria. Materials and Methods. For this study, relevant information was procured from the inhabitants via a structured questionnaire to procure the general knowledge of antimalarial medicinal plants. Results and Discussion. A total of 90 interviewees (44 men and 46 women) were involved in this survey. A total of 59 medicinal species were identified, which were dispersed in 33 families (Asteraceae (6), Apocynaceae (5), Anacardiaceae, Annonaceae, Fabaceae, Malvaceae, Meliaceae, Poaceae, and Rubiaceae (3 each), Phyllanthaceae (2)) totaling 49% of the cited species. The most cited plants are Azadirachta indica (42), Mangifera indica (38), Carica papaya (28), Cymbopogon citratus (27), Cassia fistula (15), Morinda lucida (14), Anacardium occidentale and Vernonia amygdalina (13 each), Helianthus annuus (11), Enantia chlorantha (10), and Moringa oleifera (9) A total of 105 citations were recorded for the plant parts used (leaf (46), bark (17), fruits (9), root (9), latex (11), stem (11), and inflorescence (2)) while decoction (59%), maceration (25%), infusion (9%), and exudation (7%) were the methods of preparation. Use Values (UVs) of 0.47 to 0.11 were recorded for the frequently used antimalarial plants. The Efficiency Levels (ELs) of 11 different medicinal plants stated by the respondents were Azadirachta indica, Cassia fistula and Morinda lucida (12), Chromolaena odorata (10), Mangifera indica, Enantia chlorantha and Helianthus annuus (8), Cymbopogon citratus (7), Gossypium arboretum (4), Landolphia dulcis (3), and Aloe vera (2) Cocos nucifera, Curcuma longa, Forkia biglobosa, and Musa acuminate are mentioned for the first time in the study area with little or no reported antiplasmodial activities. Conclusion. The study appraised the commonly used antimalarial plants in the study areas. Therefore, commitment to scientifically explore the bioactive compounds, antimalarial potential and toxicological profile of these plants is inevitable as they could lead to novel natural products for effective malaria therapy.